Runaway Bride - Garry, Marshall; Meloni, Christopher; Hector Elizondo; Joan Cusack; Paul Dooley; Richard Gere; Rita Wilson; Julia Roberts (USA Paramount, 1999)
Ike Graham, New York columnist, writes his text always at the last minute. This time, a drunken man in his favourite bar tells Ike about Maggie Carpenter, a woman who always flees from her grooms in the last possible moment. Ike, who does not have the best opinion about females anyway, writes an offensive column without researching the subject thoroughly. The next day, Ike gets fired by his publisher (and former wife), because he went too far and faked the facts, which real journalists don't do. Ike's only way back into the business now is to do a fact-based report on Maggie and her upcoming fourth wedding attempt, which Ike predicts to fail again. So, as he circles her like a vulture his prey-to-be, Maggie's opinion of Ike sinks below zero. Not only is Ike waiting for her to fail again but the whole town is poking fun at Maggie about her mistakes. But that is a point which Ike doesn't like.
A reporter is assigned to write a story about a woman who has left a string of fiances at the altar.
Josann McGibbon
Languages: Turkish, English Subtitles: Turkish, English
Keywords: Romance; Comedy